STUDI KONTAMINASI ASPERGILLUS FLAVUS DAN PARASITICUS PADA MAKANAN BERBAHAN BAKU KACANG TANAH - Juni Gressilda Sine (CHMK HEALTH JOURNAL, 2018)
This study was conducted to determine the presence or absence of Aspergillus flavus and Aspergillus parasiticus contamination on some types of food made from raw peanuts marketed in the city of Denpasar. Sampling method was done by purposive sampling. Determination of selected samples are five types of foods made from raw peanuts, namely salted peanuts, peanuts, peanut rempeyek, peanut enting and peanut seasoning. Samples were taken randomly as many as two brands of products from five types of food made from raw peanuts and for each type of food. Determination of sampling is a supermarket and traditional markets in Denpasar, where supermarkets and traditional markets are taken 30 percent from the number of supermarkets and traditional markets that exist. The results of this study indicate that in supermarkets, the highest population of A.flavus was found in RK2 of 320 x 103 Cfu / g and the lowest in BP1 of 40 x 103 Cfu / g, whereas A.parasiticus population was found only in RK1 of 40 x 103 Cfu / g. In traditional markets, the highest population of A.flavus was found in RK2 of 440 x 103 Cfu / g and lowest in KK1 of 40 x 103 Cfu / g, whereas A.parasiticus populations were found in RK1 and KK2 of 40 x 103 Cfu / g.Keywords: Contamination, A.flavus, A.parasiticus, Raw material of Peanut